2016
DOI: 10.1016/j.jocrd.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive factors predicting checking, procrastination and other maladaptive behaviours: Prospective versus Inhibitory Intolerance of Uncertainty

Abstract: Intolerance of Uncertainty (IU) is a cognitive construct which is strongly linked to psychopathology, particularly anxiety and obsessive-compulsive symptoms. IU has also been proposed to be linked to maladaptive behaviours such as checking and procrastination in uncertain situations. Additionally, two subfactors of IU have recently been identified, Prospective IU (Desire for Predictability) and Inhibitory IU (Uncertainty Paralysis). These factors may differentially predict approach and avoidance behaviours res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 39 publications
3
25
0
1
Order By: Relevance
“…For example, Prospective IU might drive several dysfunctional approach behaviors typical of GAD (i.e., worry) and OCD (i.e., compulsions), which are performed to reduce uncertainty/increase certainty; on the opposite, inhibitory IU would be more involved in disorders relying on avoidance behaviors to reduce exposure to uncertainty, as for example panic disorder, social anxiety, and depression [33, 34, 40]. However, findings from other studies [55, 89, 90] found that the two IU components were similarly associated with different symptom dimensions, consistent with the notion that people with high levels of IU might endorse both approach- and avoidance-oriented coping strategies to manage uncertainty and related distress but perhaps use them differentially in different situations. Consequently, the general trait IU is likely to have higher trans-diagnostic predictive utility than Prospective and Inhibitory IU separately [43].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Prospective IU might drive several dysfunctional approach behaviors typical of GAD (i.e., worry) and OCD (i.e., compulsions), which are performed to reduce uncertainty/increase certainty; on the opposite, inhibitory IU would be more involved in disorders relying on avoidance behaviors to reduce exposure to uncertainty, as for example panic disorder, social anxiety, and depression [33, 34, 40]. However, findings from other studies [55, 89, 90] found that the two IU components were similarly associated with different symptom dimensions, consistent with the notion that people with high levels of IU might endorse both approach- and avoidance-oriented coping strategies to manage uncertainty and related distress but perhaps use them differentially in different situations. Consequently, the general trait IU is likely to have higher trans-diagnostic predictive utility than Prospective and Inhibitory IU separately [43].…”
Section: Discussionmentioning
confidence: 99%
“…The internal consistency of the measure has been demonstrated across numerous clinical populations including those with OCD (Jacoby et al, 2013) as well as anxiety and depression (McEvoy and Mahoney, 2011). The IUS-12 has also been established as a reliable measure of IU in non-clinical populations (Fourtounas and Thomas, 2016). The construct validity of the IUS-12 has been demonstrated in several studies (Carleton et al, 2007;Jacoby et al, 2013).…”
Section: The Depression Anxiety Stress Scale (Dass-21)mentioning
confidence: 97%
“…IU is higher in those with OCD (Wheaton and Ward, 2020) and is also associated with subclinical obsessive-compulsivetype symptoms and need for control (Fourtounas and Thomas, 2016). Control may be particularly important as preppers display a large need to exert control over their environment (Fetterman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] For example, the Prospective IU subscale seems to be more related to GAD and obsessive-compulsive disorder (OCD) symptoms, while Inhibitory IU is more associated with symptoms of social phobia, panic disorder, post-traumatic stress disorder (PTSD), and depression. 10,11,14,15 Evidence of convergent validity, discriminant validity, and factor stability has been established. 10 The IUS-12 exhibits a strong correlation with the IUS-27 (r = 0.96) and subsequent analyses with IUS-12 using large samples demonstrated the reliability of the two-factor structure.…”
Section: Study Of Correlations Between Iu and Other Mainmentioning
confidence: 99%